Expression and significance of microRNA‐126 and VCAM‐1 in placental tissues of women with early‐onset preeclampsia - Liu, Beibei; Liu, Ling; Cui, Shihong; Qi, Yue; Wang, Tiantian (The journal of obstetrics and gynaecology research, 2021)
Objective To investigate the expression of microRNA‐126 (miR‐126) and vascular endothelial cell adhesion molecule‐1 (VCAM‐1) in the placental tissues of women with early‐onset preeclampsia (EOPE) and their effects on trophoblast invasion. Materials and Methods The placental tissues of 30 pregnant women with EOPE who delivered in the Third Affiliated Hospital of Zhengzhou University from November 2019 to May 2020 were selected as the preeclampsia (PE) group, and the placental tissues of 30 healthy pregnant women with normal prenatal examination were selected as the normal group. Immunohistochemistry was used to localize VCAM‐1 in placental tissues，the expression of miR‐126 and VCAM‐1 in placenta tissues of two groups and HTR‐8/SVneo cells transfected with miR‐126 were detected by real‐time polymerase chain reaction (RT‐PCR) and Western blot, and the correlation between them was analyzed. The invasion ability of cells transfected with miR‐126 was observed by Transwell invasion test. Results Compared with the normal group, the expression of miR‐126 was higher and VCAM‐1 was lower in the placental tissues of the PE group, and the difference were statistically significant (p < 0.01). Moreover, VCAM‐1 was negatively correlated with the expression of miR‐126 (r = −0.391, p < 0.05). In vitro experiment, the expression level of VCAM‐1 in miR‐126 mimics transfection group was decreased, and the expression level of VCAM‐1 in miR‐126 inhibitor transfection group was increased; the invasion ability of HTR‐8/SVneo cells transfected with miR‐126 mimics was decreased, and the invasion ability of HTR‐8/SVneo cells transfected with miR‐126 inhibitor was enhanced. Conclusion There was a negative correlation between the expression of miR‐126 and VCAM‐1 in EOPE.MiR‐126 and VCAM‐1 may participate in the occurrence and development of EOPE by affecting the invasion ability of trophoblast cells.